How do you evaluate e^( ( pi)/4 i) - e^( ( 11 pi)/8 i) using trigonometric functions?

1 Answer
Aug 13, 2018

The answer is =sqrt2/2-sqrt(2-sqrt2)/2+i(sqrt2/2-sqrt(2+sqrt2)/2)

Explanation:

Apply Euler's Identity

e^(itheta)=costheta+isintheta

e^(ipi/4)=cos(pi/4)+isin(pi/4)

=sqrt2/2+isqrt2/2

e^(i11/8pi)=cos(11/8pi)+isin(11/8pi)

cos(2theta)=2cos^2theta-1

costheta=sqrt((1+cos2theta)/2)

cos(11/8pi)=sqrt((1+cos(11/4pi)/2)

=sqrt((1-sqrt2/2)/2)

=sqrt(2-sqrt2)/2

cos(2theta)=1-2sin^2theta

sintheta=sqrt((1-cos(2theta))/2)

sin(11/8pi)=sqrt((1-cos(11/4pi))/2)

=sqrt((1+sqrt2/2)/2)

=sqrt(2+sqrt2)/2

Finally,

e^(ipi/4)-e^(i11/8pi)

=sqrt2/2+isqrt2/2-sqrt(2-sqrt2)/2-isqrt(2+sqrt2)/2

=sqrt2/2-sqrt(2-sqrt2)/2+i(sqrt2/2-sqrt(2+sqrt2)/2)